Response of castor (Ricinus communis L.) to polymeric bio-formulation based seed coating for drought stress: Response of castor (Ricinus communis L.) to polymeric bio-formulation based seed coating for drought stress - K S V POORNA CHANDRIKA; M BHASKAR REDDY; P LAKSHMAMMA; R D PRASAD; VARSHA GODBOLE (Journal of Oilseeds Research, 2020)
Polymer based bio-formulations for seed treatment is one of the strategies to mitigate drought stress. Drought tolerant strain of Trichoderma asperellum N13 (TN13) along with polymers was evaluated in castor under drought conditions in both glass house and field.